2009
DOI: 10.1002/ijc.24112
|View full text |Cite
|
Sign up to set email alerts
|

A‐FABP, a candidate progression marker of human transitional cell carcinoma of the bladder, is differentially regulated by PPAR in urothelial cancer cells

Abstract: Superficial pT1 bladder tumors are characterized by a high risk of recurrence and progression in grade and stage. Few studies provided evidence that loss of adipocyte-fatty acid binding protein (A-FABP) expression was associated with bladder cancer progression. A-FABP is a lipid binding protein playing a role in intracellular lipid transport and metabolism, as well as in signal transduction. We reported from bladder tumors that decrease of A-FABP transcript level significantly correlated to tumor stage and to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
54
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(59 citation statements)
references
References 49 publications
5
54
0
Order By: Relevance
“…FABP4 expression has been reported in various types of tumors such as ovarian and bladder cancers (10,22), and FABP5 (E-FAPB) has been found in oral SCC (23,24). However, the expression and exact role of FABP4 in oral SCC have not been widely investigated In the present study, using an immunohistochemical approach, we consistently found significantly higher expression of FABP4 protein in the tumor area of tongue SCC than in the non-tumor area in the same tissue samples.…”
Section: Discussionsupporting
confidence: 68%
“…FABP4 expression has been reported in various types of tumors such as ovarian and bladder cancers (10,22), and FABP5 (E-FAPB) has been found in oral SCC (23,24). However, the expression and exact role of FABP4 in oral SCC have not been widely investigated In the present study, using an immunohistochemical approach, we consistently found significantly higher expression of FABP4 protein in the tumor area of tongue SCC than in the non-tumor area in the same tissue samples.…”
Section: Discussionsupporting
confidence: 68%
“…This profile is characteristic of tumour suppressor genes. This possibility was previously evoked for FABP4 for the majority of bladder cancer (27). Gene expression correlation analyses showed a moderate correlation between TAGLN and NNMT [r(Pearson) = 0.59; p<0.001], and GDP1 (GPDA) and FABP4 [r(Pearson) = 0.57; p<0.001].…”
Section: Guaa) Gapdh (G3p) Cfl1 (Cof1) Gpd1 (Gpda) a Tendency Wasmentioning
confidence: 71%
“…FABP4 expression is down-regulated in breast cancer cell lines in comparison with normal breast cell lines (29). In bladder transitional cell carcinoma, FABP4 protein and RNA have been found significantly decreased with increasing tumour stage and histological grade, and it has demonstrated a good prognostic value (27,30).…”
Section: Discussionmentioning
confidence: 99%
“…The pathological role of FABP4 is largely different among carcinomas, as it is suppressive in bladder (17,41) and breast carcinomas (18) and stimulatory in gastric (14) and ovarian carcinomas (15). FABP4 expression was identified in almost all the tongue carcinomas examined.…”
Section: Discussionmentioning
confidence: 99%
“…The ectopic expression of FABP4 in carcinomas of the stomach (14) and ovary (15) facilitates disease progression, whereas it is downregulated in aggressive subsets of bladder and breast carcinomas (16)(17)(18). These data suggest the differential role of FABP4 in carcinomas depending on the tissue origin.…”
Section: Introductionmentioning
confidence: 99%